SARS-CoV-2 antibody response after BBIBP-CorV (Sinopharm) vaccination in cancer patients: A case-control study - Safarnezhad Tameshkel, Fahimeh; Abedin Dargoush, Shabnam; Amirkalali, Bahareh; Javadi, Saeedeh; Ghiaseddin, Ali; Alimohamadi, Yousef; Basi, Ali; Jamshidi Makiani, Mahin; Zamani, Farhad; Karbalaie Niya, Mohammad Hadi (Frontiers in Medicine, 2023)
Background: Long-term safety and efficacy of the Sinopharm vaccine especially in individuals with chronic diseases, like cancer, is under investigation. In the present prospective study, we aimed to evaluate the SARS-CoV-2 antibody response with the Sinopharm vaccine in Iranian cancer patients. Methods: All the patients registered to receive the Sinopharm vaccine were divided into two groups with (cases = 107) and without (controls = 45) history of cancer. Serum levels of SARS-CoV anti-sRBD and anti-N IgG serum levels were measured on days 0 (phase 0), 28-32 (phase I), and 56-64 (phase II) of vaccination. The data were analyzed using SPSS, version 22. Results: Totally, 152 individuals (67.1% females) with the mean age of 46.71±15.36 years were included. Solid cancers included 87.8% of the cancer cases (46.7% gynecological and 31.8% gastrointestinal cancer). At Phases, I and II, positive anti-sRBD IgG and anti-N IgG were significantly lower among the cases in the total analysis. Side effects were not significantly different between the cases and controls. The lowest positive anti-sRBD IgG test was observed among the cancerous patients who were simultaneously receiving chemotherapy (35.3%). Anti-sRBD IgG and anti-N IgG serum levels significantly increased at phases I and II in the total analysis and in each group. In addition, serum anti-sRBD IgG increased during the three phases and it was significantly higher in the control group. Conclusions: Cancerous patients have lower antibody response after full vaccination with BBIBP-CorV (Sinopharm). Males, older individuals, individuals with BMI≥25, those without past history of COVID-19, and with hematologic cancers were more possible to have no antibody response. No significant side effects after vaccination were seen.